Query Response Time Comparison SQL and No SQL for Contact Tracing Application - Arik Bagus Setyawan; Irwan Alnarus Kautsar; Nuril Lutvi Azizah (Universitas Muhammadiyah Sidoarjo, 2022)
During the current Covid-19 pandemic, it is necessary to have facilities to track community activities to make it easier to cope with the Covid-19 pandemic situation which is still a threat to the community. Contact tracing application (Contact Tracing) is one solution that can be used in this regard. By utilizing Contact Tracing, people's activities can be recorded when traveling to meet other people so that they can generate a history that can be used to track someone if one of them is infected with Covid-19. With this application, data storage (database) is very important because the application will generate and consume a lot of data. In this study, the researcher attempted to compare the query speed of the common data storage (database) that is usually used, namely Relational Database (MySQL) with Non-Relational Database (MongoDB). The results of the experiments conducted by the researchers resulted in the Non-Relational Database (MongoDB) suitable for use when the data has reached large amounts because the query speed is quite fast and stable. Meanwhile, Relational Database performance is still reliable when the data query needs are only on a small scale.